USING TIKTOK TO PRACTICE SPEAKING SKILLS: EXPERIENCE OF INDONESIAN UNIVERSITY STUDENTS - Nurwinda, Sulistia; Ambarwati, Evi Karlina (STKIP Persada Khatulistiwa Sintang, 2024)
The rise of technology has led to an increase in the use of technology in education. There are a lot of platforms that can be used for a learning medium, one of them is TikTok. TikTok is a video-sharing app where users can watch or create short videos with various topics, including education. This research was conducted to find out students' experiences while using the TikTok platform as a learning medium to practice speaking skills. This research utilized a qualitative design with a case study as a method. To gain a comprehensive understanding of the participants' experience using TikTok as a learning tool, the research employed a combination of interviews and questionnaires as instruments. This research involved five English education department students as participants. The findings of this research revealed that all participants had a positive experience using TikTok as a learning tool to practice speaking. The study found that participants not only loved TikTok's easy navigation and engaging content but also appreciated its interactive features, particularly the